2006
DOI: 10.1128/ec.5.4.753-761.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cell Division of Giardia intestinalis : Flagellar Developmental Cycle Involves Transformation and Exchange of Flagella between Mastigonts of a Diplomonad Cell

Abstract: Giardia intestinalis is a binucleated diplomonad possessing four pairs of flagella of distinct location and function. Its pathogenic potential depends on the integrity of a complex microtubular cytoskeleton that undergoes a profound but poorly understood reorganization during cell division. We examined the cell division of G. intestinalis with the aid of light and electron microscopy and immunofluorescence methods and present here new observations on the reorganization of the flagellar apparatus in the dividin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 31 publications
10
103
0
1
Order By: Relevance
“…4B). These data confirm and extend a recent report of flagellar rearrangements during mitosis in Giardia (Nohynkova et al, 2006).…”
Section: Flagellar Duplicationsupporting
confidence: 82%
See 1 more Smart Citation
“…4B). These data confirm and extend a recent report of flagellar rearrangements during mitosis in Giardia (Nohynkova et al, 2006).…”
Section: Flagellar Duplicationsupporting
confidence: 82%
“…This basal body, with its associated flagellum, may play an indirect role in spindle nucleation and organization; its association with a spindle pole may ensure its proper segregation to the daughter cells. Our data support the recent description of movements of flagellar complexes during cell division (Nohynkova et al, 2006).…”
Section: Evidence For Kinetochore Microtubules In Chromosome Segregationsupporting
confidence: 81%
“…During mitosis, the anterior, dorsal, and ventral flagella pairs (Fig. 2B) are repositioned by an unknown mechanism (21,22). Coincidentally, a cloud of actin was observed around the corresponding internal axonemes.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, it is impossible to separate our understanding of the duplication and segregation of centrosomes and basal bodies from the wider implications for cell morphogenesis. In many cells, light microscopy has shown that morphogenesis involves particular centrosomal or basal body movements, and electron microscopy has allowed the definition of the arrangements of component filaments and rootlets (Brugerolle, 1992;Nohynkova et al, 2006;Wright et al, 1985). In only a few cases do we know much about the detailed coordination of centrosomal/basal body duplication in terms of the subsequent inheritance of cell pattern and polarity.…”
Section: Discussionmentioning
confidence: 99%